(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2020)
The article describes various types of single-layer and double-layer diagrid structures. Types variants of diagrid structures that are used more for public buildings are given. The diagrid systems structural forms of existing types analysis, identified disadvantages and advantages of such structures. The calculating diagrid structural systems features using modern software systems are revealed. A new type of flat diagrid structures in the form of regular hexagons made of bent profiles is proposed. The variants of this structure type manufacturing and joining elements are considered. The bent channels and bolted dimensions or self-tapping screw systems are determined by calculation